Efficacy in-vivo of Different Fungicides in Controlling Stemphylium Blight of Lentil During 1998-2001 (Bangladesh Journal of Scientific and Industrial Research, 2007)
In an experiment with seven different fungicides such as Rovral 50WP @ 0.2 %, Dithane M-45 @ 0.2 %, Tilt 250EC @ 0.05 %, Cupravit @ 0.3 %, Macuprax @ 0.25 %, Ridomil MZ-72 @ 0.2 % and Bavistin 50WP @ 0.15 % were tested in the field during 1998-2001 to control Stemphylium blight lentil. Among the fungicides Rovral 50WP @ 0.2 % was noted as the most effective fungicide followed by Dithane M-45 @ 0.2 % and Tilt 250EC @ 0.05 %. Bangladesh J. Sci. Ind. Res. 42(1), 89-96, 2007